DOI: 10.25148/etd.fi15101911
|View full text |Cite
|
Sign up to set email alerts
|

Biology and use of nibbi heteropsis flexuosa (ARACEAE) the source of an aerial root fiber product in Guyana

Abstract: Hoffman, Bruce, "Biology and use of nibbi heteropsis flexuosa (ARACEAE) the source of an aerial root fiber product in Guyana" (1997). This thesis, written by Bruce Hoffman, and entitled "Biology and use of Nibbi Heteropsis flexuosa (Araceae): the source of an aerial root fiber product in Guyana", having been approved in respect to style and intellectual content, is referred to you for judgment.We have read this thesis and recommend that it be approved. With present methods, harvest does not decimate population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
3
12

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 12 publications
2
11
3
12
Order By: Relevance
“…6A, B). A similar observation was reported by Hoffman (1997) in his study of this species in the Guianas and by Fadiman (2003) in H. ecuadorensis in Ecuador. In another case in the Reserva Ducke, an individual that had fallen to the forest floor together with its host tree was observed producing flagelliform branches from the apex of a plagiotropic shoot as well as from the main shoot, each seeking a new host (Figs.…”
Section: ] Soares Et Al: Heteropsissupporting
confidence: 69%
See 2 more Smart Citations
“…6A, B). A similar observation was reported by Hoffman (1997) in his study of this species in the Guianas and by Fadiman (2003) in H. ecuadorensis in Ecuador. In another case in the Reserva Ducke, an individual that had fallen to the forest floor together with its host tree was observed producing flagelliform branches from the apex of a plagiotropic shoot as well as from the main shoot, each seeking a new host (Figs.…”
Section: ] Soares Et Al: Heteropsissupporting
confidence: 69%
“…Recent studies like that of Hoffman (1997) report the use of the roots of Heteropsis flexuosa by the Wai-Wai people of southeast Guyana for different types of cordage, baskets, bags, brooms, furniture, and other craft products as well as a head decoration in ceremonies to invoke the sun. Plowden et al (2003) reported the use of this cipó (H. flexuosa) for various purposes including binding in house-building in two indigenous reserves on the upper Rio Guamá in Pará state.…”
Section: ] Soares Et Al: Heteropsismentioning
confidence: 99%
See 1 more Smart Citation
“…Bunting (Araceae) and Clusia spp. (Clusiaceae) as raw material (Hoffman 1997, van Andel 2000, Wallace & Ferreira 2000.…”
Section: Ethnobotany Research and Applications 244mentioning
confidence: 99%
“…The harvest of aerial roots of hemiepiphytes for the manufacture of wicker furniture and basketry is a promising business in the Amazon Basin (Baluarte & del Castillo 2001, Hall 2000, Hoffman 1997, Plowden et al 2003, Whitehead & Godoy 1991. Hemiepiphytes are relatively abundant and their aerial roots can easily be pulled down.…”
Section: Introductionmentioning
confidence: 99%